Reusability of pre-treatment water obtained via textile wastewater by coagulation and filtration methods in reactive and disperse dyeing - Turgut, Halil İbrahim (İdris Karagöz, 2024)
Besides high-water consumption in the textile industry, color, quantity, and variety of chemicals in discharged wastewater draws attention both in terms of environmental and economic aspects. Therefore, efficient, and reliable treatment techniques are needed. In this context, coagulation is a very important step in the treatment of wastewater. In this study, water recovery from textile wastewater taken from different discharge points was investigated by using coagulation and filtration methods. Iron (III) chloride hexahydrate (FeCl3.6H2O) was used as a coagulant. The optimum conditions were determined by studying the effect of different coagulant dosages and pH values. The filtration process was performed using 12-25 µm and

Tekstil sektöründe yüksek su tüketiminin yanı sıra deşarj edilen atık sudaki kimyasalların rengi, miktarı ve çeşitliliği hem çevresel hem de ekonomik açıdan dikkat çekmektedir. Bu nedenle etkin ve güvenilir tedavi tekniklerine ihtiyaç vardır. Bu bağlamda atık suyun arıtımında pıhtılaşma çok önemli bir adımdır. Bu çalışmada farklı deşarj noktalarından alınan tekstil atık sularından koagülasyon ve filtrasyon yöntemleri kullanılarak su geri kazanımı araştırılmıştır. Pıhtılaştırıcı olarak demir (III) klorür heksahidrat (FeCl3.6H2O) kullanıldı. Optimum koşullar, farklı pıhtılaştırıcı dozajlarının ve pH değerlerinin etkisi incelenerek belirlendi. Filtrasyon işlemi 12-25 µm ve
Tekstil atık suyundan koagülasyon ve filtrasyon yöntemleriyle elde edilen ön arıtma suyunun reaktif ve dispers boyamalarda yeniden kullanılabilirliği
HRPT-PR-K26
Keywords: Wastewater Treatment Processes; Atıksu Arıtma Süreçleri